Patient Experience on Nursing Care and Patient Loyalty; A Lesson Learn from Regional Public Hospital in Indonesia - Fitriani Mursyid; Muhammad Ikhtiar; Andi Rizki Amelia; Rezky Aulia Yusuf (Jurnal Ekonomika, 2022)
Patient experience has been identified as an important indication of healthcare quality, and accreditation authorities utilize it to assess hospital treatment. A high proportion of health caregivers are nurses. The services provided by nurses are significantly influential in the experience and satisfaction of patients. However, few studies in the developing settings were conducted to understand the types of relationship that exists between patient loyalty and patient experience. This study aims to describe the relationship between patient experience and patient loyalty at Majene Hospital. This is a cross-sectional study with a total respondence were 246 patients. The data was collected through interviews using a questionnaire. Analysis of the chi-square test data and the Pearson correlation test with the significance value of p < 0.05 was used, by SPSS 20. There is a significant relationship between patient experience and patient loyalty at the inpatient installation of Majene Hospital with (p-value <0.05). The results of the multivariate analysis obtained that the most significant relationship is the experience in post-hospital nursing transition with a significance value of 0.000 < 0.05 and a correlation value of 0.348. At the same time, the lowest correlation value is the experience on nurse communication, 0.212. There is a significant relationship between the six dimensions of patient experience on nursing care with patient loyalty. This research suggests further improving nurses' therapeutic communication through training in effective communication and responsiveness of staff and the health of the hospital environment, further improving the responsiveness of health workers, providing suggestion boxes, and following up on suggestions given by patients.